Code-Mixing and Code Switching: A Special Issue in ELT - Tumbahang, Mohan Kumar (Researcher: A Research Journal of Culture and Society, 2020)
The aim of this article is to offer a brief discussion on the issue of code-mixing and code-switching which has played crucial but controversial role in the foreign language teaching-learning activities more specifically in the English Language Teaching (ELT). The methodology used in this article is essentially the descriptive one which deals with the non-numerical data to explain and analyze the proposed issue. The basic theory has been drawn from the sociolinguistics that generally discusses on the bilingualism as well as multilingualism where the notion of code-mixing and code-switching have become universal phenomenon. This paper can be helpful for the students, teachers, textbook writers and the beginners of the ELT practitioners.